Hubungan antara Konsep Diri dengan Kecemasaan saat Berbicara di Depan Umum pada Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta - Rika Wati, Mita; , Dra. Partini, M.Si (2015)
Students of psychology faculty are required to have the ability to speak in public, in addition to expressing his thoughts in writing. The ability to express something verbally require a good mastery of language to be easily understood by others and require self tepa pembawan associated with the concept of a person. This study aims to determine the relationship between self-concept Kecemasaan Public Speaking at the front of the Faculty of Psychology, University Muhammadiayah Surakarta. Researchers chose quantitative methods to achieve the objectives of this research. Subjects used in this study is the Student of 2013, which amounted to ± 290 people and taken a sample of 53 people. Results of the correlation coefficient (r_xy) of -0.293 with p value = 0.017 <0.05, which means there is a significant negative correlation between self-concept and anxiety of public speaking. Based on the results of analysis variables self-concept has the empirical mean (RE) of 63.13 and the mean hypothetical (RH) of 55, which means self-concept research subject is high. Public speaking anxiety variables having the empirical mean (RE) of 50.09 and the mean hypothetical (RH) of 50 which means anxiety public speaking on the subject of the study was moderate.